2018
DOI: 10.2147/ijn.s97572
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicine applications in women's health: state of the art

Abstract: State-of-the-art applications of nanomedicine have the potential to revolutionize the diagnosis, prevention, and treatment of a range of conditions and diseases affecting women’s health. In this review, we provide a synopsis of potential applications of nanomedicine in some of the most dominant fields of women’s health: mental health, sexual health, reproductive medicine, oncology, menopause-related conditions and dementia. We explore published studies arising from in vitro and in vivo experiments, and clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 202 publications
(187 reference statements)
0
19
0
Order By: Relevance
“…Overall, the data showed that SLNs can be used to improve the efficacy of antidepressants [ 68 ]. In another research study where the antidepressant, duloxetine was encapsulated in SLNs, the oral bioavailability of the drug was improved owing to reduced first-pass metabolism of the duloxetine-SLN system when compared with duloxetine only [ 69 ]. The drug–nanoparticle formulation was stable under acidic media and it displayed improved pharmacological properties in vivo.…”
Section: Nanocarriers Employed As Therapeutic Delivery Platforms Of Antidepressantsmentioning
confidence: 99%
“…Overall, the data showed that SLNs can be used to improve the efficacy of antidepressants [ 68 ]. In another research study where the antidepressant, duloxetine was encapsulated in SLNs, the oral bioavailability of the drug was improved owing to reduced first-pass metabolism of the duloxetine-SLN system when compared with duloxetine only [ 69 ]. The drug–nanoparticle formulation was stable under acidic media and it displayed improved pharmacological properties in vivo.…”
Section: Nanocarriers Employed As Therapeutic Delivery Platforms Of Antidepressantsmentioning
confidence: 99%
“…Magnetic nanoparticles are ever used in nanostructured bisphosphonate (Bis)-conjugated iron (II, III) oxide (Fe3O4), while hydroxyapatite nanoparticles are used in nanostructured risedronate/ zinchydroxyapatite. 25 A nanoparticle is a term for a particle that has a size of less than 100 nm. 26 The bone structure is composed of nano-sized components that using a nanoparticle to target this site is no longer an impossible mission.…”
Section: Magnetic Nanoparticle As Osteoporosis Therapymentioning
confidence: 99%
“…Nanomedicine is the application of the principles and methods of nanoscience and technology to medicine, aimed at developing more sensitive and rapid medical methods and understanding the processes and mechanisms of life activities at the more micro or nano level (Albanese, Tang, & Chan, 2012; Bregoli et al, 2016; Emerich, 2005; Lloyd‐Parry, Downing, Aleisaei, Jones, & Coward, 2018). Worldwide it is evident that there is increasing emphasis on biomedical applications of a wide range of nanomaterials including silica nanoparticles (SNPs), superparamagnetic iron oxide nanoparticles, gold nanoparticles, and graphene and metal organic frameworks (Cheng, Deng, Lin, Cai, & Zink, 2019; Darweesh, Ayoub, & Nazzal, 2019; Rive et al, 2019; Yan et al, 2019; Zhong, Kankala, Wang, & Chen, 2019).…”
Section: Introductionmentioning
confidence: 99%